A global assessment of the prevalence of current and potential future infrastructure in Key Biodiversity Areas. (May 2023) - Simkins, Ashley T.; Beresford, Alison E.; Buchanan, Graeme M.; Crowe, Olivia; Elliott, Wendy; Izquierdo, Pablo; Patterson, David J.; Butchart, Stuart H.M.
Abstract: Infrastructure development is a major threat to biodiversity, leading to habitat loss and fragmentation, increased accessibility and pollution. Key Biodiversity Areas represent the most comprehensive network of important areas for biodiversity and the prevalence of infrastructure in KBAs has not previously been described. Here we examined the prevalence of current and potential future infrastructure within the global network of 15, 150 terrestrial KBAs, using a range of open and commercial spatial datasets related to infrastructure. Current infrastructure types analysed included transport, energy, extractives, urban areas, and dams and reservoirs. At least 80 % of KBAs contain infrastructure, and roads occurred in 75.1 % of KBAs. Potential future development of mines, oil and gas infrastructure and powerplants suggests a significant increase in the number of KBAs that may contain these infrastructure types in the future (e.g. by 292 % for mines)), disproportionately in countries in the Global South. Further work is needed to determine how different infrastructure types affect the species and ecosystems for which KBAs have been identified. More effective application and wider adoption of safeguards are needed to ensure infrastructure development avoids serious negative impacts on biodiversity. Highlights: Infrastructure development poses one of the greatest threats to biodiversity. Most Key Biodiversity Areas (KBAs) contain/are projected to contain infrastructure. KBAs in countries in the Global South have a disproportionate risk of future development. KBAs need stronger safeguards to avoid negative impacts of further development. Need to understand how infrastructure impacts species and ecosystems within KBAs.